How diploidization turned a tetraploid into a pseudotriploid - Mandáková, Terezie; Gloss, Andrew D; Whiteman, Noah K; Lysak, Martin A (American journal of botany, 2016)
PREMISE OF THE STUDY: Despite being highly fertile and occupying a large geographic region, the North American heartleaf bittercress (Cardamine cordifolia; Brassicaceae) has a puzzling triploid-like chromosome number (2n = 3x = 24). As most triploids are sterile, we embarked on a detailed analysis of the C. cordifolia genome to elucidate its origin and structure. METHODS: Mitotic and meiotic chromosome complement of C. cordifolia was analyzed by comparative chromosome painting using chromosome-specific BAC contigs of Arabidopsis thaliana. Resulting chromosome patterns were documented by multicolor fluorescence microscopy and compared with known ancestral and extant Brassicaceae genomes. KEY RESULTS: We discovered that C. cordifolia is not a triploid hybrid but a diploidized tetraploid with the prevalence of regular, diploid-like meiotic pairing. The ancestral tetraploid chromosome number (2n = 32) was reduced to a triploid-like number (2n = 24) through four terminal chromosome translocations. CONCLUSIONS: The structure of the pseudotriploid C. cordifolia genome results from a stepwise diploidization process after whole-genome duplication. We showed that translocation-based descending dysploidy (from n = 16 to n = 12) was mediated by the formation of five new chromosomes. The genome of C. cordifolia represents the diploidization process in statu nascendi and provides valuable insights into mechanisms of postpolyploidy rediploidization in land plants. Our data further suggest that chromosome number alone does not need to be a reliable proxy of species' evolutionary past and that the same chromosome number may originate either by polyploidization (hybridization) or due to descending dysploidy.
Keywords: dysploidy; polyploidy; diploidization; malování chromozomů; zeměpis; genom rostlinný; Genome, Plant; whole-genome duplication; karyotype evolution; Chromosome Painting; triploidie; chromosome translocation; karyotyp; ploidie; biologická evoluce; Cardamine; Brassicaceae; Geography; chromozomy rostlin; Chromosomes, Plant; centromere loss; Biological Evolution; chromosome fusion; Hybridization, Genetic; tetraploidie; hybridizace genetická; Tetraploidy; Triploidy; Ploidies; Karyotype